Risankizumab for Ulcerative Colitis Two Randomized Clinical Trials - Louis, Edouard; Schreiber, Stefan; Panaccione, Remo; Bossuyt, Peter; Biedermann, Luc; Colombel, Jean-Frederic; Parkes, Gareth; Peyrin-Biroulet, Laurent; D'Haens, Geert; Hisamatsu, Tadakazu; Siegmund, Britta; Wu, Kaichun; et al. (American Medical Association (AMA), 2024)
IMPORTANCE The clinical effects of risankizumab (a monoclonal antibody that selectively targets the p19 subunit of IL-23) for the treatment of ulcerative colitis are unknown. OBJECTIVE To evaluate the efficacy and safety of risankizumab when administered as an induction and a maintenance therapy for patients with ulcerative colitis. DESIGN, SETTING, AND PARTICIPANTS Two phase 3 randomized clinical trialswere conducted. The induction trial was conducted at 261 clinical centers (in 41 countries) and enrolled 977 patients from November 5, 2020, to August 4, 2022 (final follow-up on May 16, 2023). The maintenance trial was conducted at 238 clinical centers (in 37 countries) and enrolled 754 patients from August 28, 2018, to March 30, 2022 (final follow-up on April 11, 2023). Eligible patients had moderately to severely active ulcerative colitis; a history of intolerance or inadequate response to 1 or more conventional therapies, advanced therapies, or both types of therapies; and no prior exposure to risankizumab. INTERVENTIONS For the induction trial, patients were randomized 2:1 to receive 1200mg of risankizumab or placebo administered intravenously at weeks 0, 4, and 8. For the maintenance trial, patients with a clinical response (determined using the adapted Mayo score) after intravenous treatment with risankizumab were randomized 1:1:1 to receive subcutaneous treatment with 180mg or 360mg of risankizumab or placebo (no longer receiving risankizumab) every 8 weeks for 52 weeks. MAIN OUTCOMES AND MEASURES The primary outcomewas clinical remission (stool frequency score ≤1 and not greater than baseline, rectal bleeding score of 0, and endoscopic subscore ≤1 without friability) at week 12 for the induction trial and at week 52 for the maintenance trial. RESULTS Among the 975 patients analyzed in the induction trial (aged 42.1 [SD, 13.8] years; 586/973 [60.1%] were male; and 677 [69.6%] were White), the clinical remission rates at week 12 were 132/650 (20.3%) for 1200mg of risankizumab and 20/325 (6.2%) for placebo (adjusted between-group difference, 14.0% [95%CI, 10.0%-18.0%], P < .001). Among the 548 patients analyzed in the maintenance trial (aged 40.9 [SD, 14.0] years; 313 [57.1%] were male; and 407 [74.3%] were White), the clinical remission rates at week 52 were 72/179 (40.2%) for 180mg of risankizumab, 70/186 (37.6%) for 360mg of risankizumab, and 46/183 (25.1%) for placebo (adjusted between-group difference for 180mg of risankizumab vs placebo, 16.3%[97.5%CI, 6.1%-26.6%], P < .001; adjusted between-group difference for 360mg of risankizumab vs placebo, 14.2%[97.5%CI, 4.0%-24.5%], P = .002). No new safety risks were detected in the treatment groups. CONCLUSION AND RELEVANCE Compared with placebo, risankizumab improved clinical remission rates in an induction trial and in a maintenance trial for patients with moderately to severely active ulcerative colitis. Further study is needed to identify benefits beyond the 52-week follow-up.